2018
DOI: 10.1002/dmrr.3060
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves hyperglycemia induced damages in rat brain

Abstract: Addition of melatonin to the insulin treatment did not change the effects of insulin, but the detailed role of melatonin alone in the treatment of diabetes merits further experimental and clinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…Treatment with MLT significantly ameliorated hyperglycemia and the reduction of insulin levels, blocked the glycosylation of hemoglobin and improved insulin resistance in T2DM rats. These results corroborate the improvement of hyperglycemia by MLT treatment in several experimental models [ 3 , 34 , 35 ]. These findings agree with the ability of MLT to reverse the reduction of GLUT4 gene expression, glucose intolerance and insulin resistance, and augmented gluconeogenesis in MLT-deficient pinealectomized rats [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Treatment with MLT significantly ameliorated hyperglycemia and the reduction of insulin levels, blocked the glycosylation of hemoglobin and improved insulin resistance in T2DM rats. These results corroborate the improvement of hyperglycemia by MLT treatment in several experimental models [ 3 , 34 , 35 ]. These findings agree with the ability of MLT to reverse the reduction of GLUT4 gene expression, glucose intolerance and insulin resistance, and augmented gluconeogenesis in MLT-deficient pinealectomized rats [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 88%
“…The Framingham study showed that diabetic men and women were, respectively, two and five times more likely to develop heart problems than nondiabetic subjects [ 2 ]. T2DM is a metabolic disorder characterized by increased resistance to insulin in glucose-sensitive tissues and dyslipidemia leading to hyperglycemia, prolonged inflammation, and oxidative stress [ 3 ]. At the advanced stage, diabetic cardiomyopathy (DCM) clinically presents as heart failure in T1DM and T2DM [ 4 ]; however, the early events during the development of T2DM-induced organ injury are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The high concentrations of MLT in mitochondria provides further evidence of its role in anti-apoptotic and anti-oxidative stress (Reiter et al, 2016). Indeed, MLT has been shown to improve the glycemic state by upregulating GSH (Gurel-Gokmen et al, 2018). MLT levels in blood is lower in diabetic patients compared to healthy individuals (Cipolla-Neto et al, 2014;Reutrakul et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In general, antioxidants stabilize cell membranes (particularly, neuronal membranes) by counteracting lipid peroxidation . Antioxidant substances are plant extracts such as chard, spirulina platensis, resveratrol, cinnamon, grape seed, melatonin, quercetin, and others. All these antioxidants have proved their beneficial protective role against tissues, lipid peroxidation, and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%